2011
DOI: 10.1044/1092-4388(2010/09-0205)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Listener Experience and Anchors on Judgments of Dysphonia

Abstract: Listeners systematically shift judgments of voice quality in response to auditory anchors. Anchors reduce interrater variability and may improve agreement across some types of listeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
17

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 34 publications
3
30
0
17
Order By: Relevance
“…Some authors believe that listeners should be trained prior to the assessment of hypernasality to adjust their internal scales, i.e., they should classify speech samples with different degrees of nasality until they reach an agreement in their own judgments (13) . Studies contemplating the auditory perceptual assessment of voice quality have shown that the use of anchors, prior listener training, and experience of the listeners favor the reliability of results (7,(14)(15)(16)(17)(18)(19) . Regarding the vocal aspects, multiple authors have demonstrated the efficacy in both the listener training and the use of anchors in the perceptual assessment of dysphonia symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors believe that listeners should be trained prior to the assessment of hypernasality to adjust their internal scales, i.e., they should classify speech samples with different degrees of nasality until they reach an agreement in their own judgments (13) . Studies contemplating the auditory perceptual assessment of voice quality have shown that the use of anchors, prior listener training, and experience of the listeners favor the reliability of results (7,(14)(15)(16)(17)(18)(19) . Regarding the vocal aspects, multiple authors have demonstrated the efficacy in both the listener training and the use of anchors in the perceptual assessment of dysphonia symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the effect of the use of anchors in perceptual assessments was compared between the experienced and inexperienced listeners with respect to voice quality (18) . They found that the three groups of listeners judged the speech samples with significantly minor severity under the conditions in which the anchors were presented and that the listeners with and without experience showed improvements in interrater agreement for tasks that used anchors.…”
Section: Introductionmentioning
confidence: 99%
“…Uma vez que muitos autores afirmam que a experiência é um fator essencial para se obter um resultado confiável na avaliação perceptivo-auditiva (LEWIS; HOUGHTON, 2003;WHITEHILL;CIOCCA, 2009;KAPSNER-SMITH, 2011), tomou-se o cuidado de selecionar profissionais experientes na avaliação de fala de indivíduos com fissura labiopalatina para participar do estudo. As três fonoaudiólogas que julgaram as amostras de fala do presente estudo tinham, no mínimo, 12 anos de experiência na área e realizaram a tarefa de classificar a hipernasalidade, individualmente, nas duas etapas do estudo.…”
Section: Discussionunclassified
“…Esta é uma das razões que levou alguns autores a defenderem a utilização do treinamento prévio dos avaliadores como estratégia para melhorar o índice de concordância de diferentes ouvintes e, assim, aumentar a confiabilidade da avaliação perceptivo-auditiva (BRADFORD; BROOKS; SHELTON, 1964;YIU, 2002;ELANDER, 2006;KAPSNER-SMITH, 2011;WATTERSON et al, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation